A hydrophilically modified polyisocyanate, its preparation and use
Patent Information
- Application Number
- CN202611016970.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-09
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]CN115010902B提出通过控制氨基磺酸的粒径分布(粒径≤900目的颗粒少于10wt%,且粒径>40目的颗粒少于10wt%)来提高反应速率与降低产品浊度和颜色,但是氨基磺酸改性多异氰酸酯产品的适用期短和涂膜耐沾污性能差
本发明无需额外添加羟基羧酸,通过使用具有特定晶型的氨基磺酸来制备水分散性多异氰酸酯,既可显著延长适用期,提高涂膜的耐沾污性能,还能缩短反应时间,降低产品浊度和色度。
Smart Images

Figure CN122917282A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polyurethane coating technology, and relates to a hydrophilic modified polyisocyanate, its preparation method and application. Background Technology
[0002] In recent years, water-dispersible polyisocyanates have been increasingly widely used in various fields due to their compliance with the stringent environmental and safety requirements of modern industry. They are commonly used as curing agents in two-component polyurethane coating systems and can also be used as additives in water-dispersible adhesives.
[0003] Currently, water-dispersible polyisocyanates are mainly classified into two types based on the type of hydrophilic groups: carboxylates and sulfonates. However, carboxylate-modified polyisocyanates are highly sensitive to pH and easily decompose upon contact with water. Therefore, in recent years, researchers have focused more on sulfonic acid-based hydrophilic modifiers. Compared with carboxylic acids, sulfonic acids have stronger hydrophilicity, allowing for further reduction in the amount of hydrophilic modifier added during modification, resulting in products with higher functionality and NCO content, thus showing better application prospects.
[0004] CN1190450C discloses the use of solid powders of 3-(cyclohexylamino)propanesulfonic acid and 2-(cyclohexylamino)ethanesulfonic acid to modify polyisocyanates, resulting in products that can be uniformly dispersed in water without high shear force. However, the heterogeneous reaction between solid powder aminosulfonic acid and polyisocyanate results in a low reaction rate, and unreacted aminosulfonic acid tends to exist in particulate form in the product, leading to high turbidity and color. In the coatings industry, compared to primers and intermediate coats, topcoats (especially clear topcoats and light-colored topcoats) have higher requirements for appearance indicators such as transparency, gloss, and texture. Therefore, water-dispersible polyisocyanates used in these topcoats must possess low turbidity and low color to ensure high transparency and a pure base color, avoiding appearance defects such as haziness, yellowing, and dullness. This better restores the original color of the substrate and the clear texture of the paint film, meeting the dual requirements of appearance and performance for high-end decoration (such as high-grade wood coatings and automotive coatings). Therefore, how to obtain sulfonic acid modified polyisocyanate products with low turbidity and low color number while increasing the reaction rate remains one of the difficulties that plagues those skilled in the art.
[0005] CN115010902B proposes to improve the reaction rate and reduce product turbidity and color by controlling the particle size distribution of aminosulfonic acid (particles with a particle size ≤900 mesh are less than 10 wt%, and particles with a particle size >40 mesh are less than 10 wt%). However, aminosulfonic acid-modified polyisocyanates have a short pot life and poor coating stain resistance. Currently, the pot life of water-dispersible polyisocyanates is generally 2-6 hours. A short pot life leads to a short application time and can even seriously affect coating performance. A coating with good stain resistance can protect the long-term appearance and quality of the product, reduce regular maintenance and cleaning, and extend the product's service life. CN116178672B proposes to improve the reaction rate, reduce product turbidity and color, and extend the pot life of modified polyisocyanates by adding hydroxycarboxylic acids. However, the hydroxyl groups in hydroxycarboxylic acids consume NCO groups, resulting in a decrease in the crosslinking density of the coating and a decline in the final coating's stain resistance. Summary of the Invention
[0006] To address the shortcomings of existing technologies, the present invention aims to provide a hydrophilic modified polyisocyanate, its preparation method, and its applications. This invention eliminates the need for the addition of hydroxycarboxylic acids, using aminosulfonic acid with a specific crystal form to prepare a water-dispersible polyisocyanate. This significantly extends the pot life, improves the stain resistance of the coating film, shortens the reaction time, and reduces product turbidity and color.
[0007] To achieve this objective, the present invention adopts the following technical solution: On one hand, the present invention provides a hydrophilic modified polyisocyanate, which is prepared by reacting raw materials comprising the following components; Component A: polyisocyanate, component B: α-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid, and component C: tertiary amine.
[0008] In this invention, α-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid is used to prepare hydrophilic modified polyisocyanate, which can significantly extend the pot life, improve the stain resistance of the coating film, shorten the reaction time, and reduce the turbidity and color of the product.
[0009] Preferably, the X-ray powder diffraction pattern of the α-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid, measured using CuKa rays, has 2θ values of 5.473±0.2°, 5.936±0.2°, 9.139±0.2°, 10.574±0.2°, 10.970±0.2°, 11.221±0.2°, 11.903±0.2°, 14.518±0.2°, 14.866±0.2°, 15.994±0.2°, 16.494±0.2°, 17.585±0.2°, 17.890±0.2°, 18.754±0.2°, and 19.011±0.2°. Characteristic peaks are observed at 21.296±0.2°, 22.035±0.2°, 22.763±0.2°, 24.967±0.2°, 26.157±0.2°, 26.660±0.2°, 28.054±0.2°, 28.787±0.2°, 29.797±0.2°, 30.992±0.2°, 31.408±0.2°, 31.965±0.2°, 34.159±0.2°, 35.004±0.2°, and 36.530±0.2°. Preferably, the X-ray powder diffraction pattern of the α-crystal form of 3-(cyclohexylamine)-1-propanesulfonic acid, measured using CuKa rays, has the strongest diffraction peak at 2θ values of 5.473±0.2° and / or 5.936±0.2°.
[0010] In this invention, 3-(cyclohexylamine)-1-propanesulfonic acid has the following structure: .
[0011] Preferably, the purity of the α-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid (CAPS) is ≥90wt%.
[0012] Preferably, in the particle size distribution of the α-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid, the content of particles with a diameter ≤16μm accounts for ≥25% (e.g., 28%, 30%, 32%, 34%, 38%, 40%, 45%, etc.).
[0013] The α-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid used in this invention can be a purchased product or a product prepared in-house.
[0014] Preferably, the method for preparing the α-crystalline form of 3-(cyclohexylamine)-1-propanesulfonic acid includes the following steps: β-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid was dissolved in a first solvent, filtered, pre-cooled, and then a second solvent was added to precipitate, filtered, and dried to obtain the α-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid. The first solvent is selected from water, methanol or ethanol, and the second solvent is selected from one or a combination of at least two of N,N-dimethylformamide, tetrahydrofuran, 1,4-dioxane, and acetone.
[0015] Preferably, the β-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid is purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. as 3-(cyclohexylamine)-1-propanesulfonic acid (analytical grade, purity ≥98%).
[0016] Preferably, the mass-to-volume ratio (m:v) of the β-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid to the first solvent is 1:3 to 1:5 (g:mL), for example, 1:3, 1:3.5, 1:3.8, 1:4, 1:4.3, 1:4.5, 1:4.8 or 1:5.
[0017] Preferably, the β-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid is dissolved in the first solvent and then stirred at 40-50°C (e.g., 40°C, 42°C, 45°C, 48°C or 50°C) for 10-40 min (e.g., 10 min, 15 min, 20 min, 25 min, 30 min, 35 min or 40 min).
[0018] Preferably, the volume ratio (v:v) of the second solvent to the first solvent is 3:1 to 10:1, for example, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1.
[0019] Preferably, the precooling is precooling to 0°C.
[0020] Preferably, the second solvent is pre-cooled to 0°C before being added to the system.
[0021] Preferably, the second solvent is added to the system in one go within 30 seconds.
[0022] Preferably, after precipitation, the mixture is stirred for 5-20 minutes (e.g., 5 minutes, 10 minutes, 15 minutes or 20 minutes) and then immediately vacuum filtered. The filter cake is then quickly washed with a second solvent and immediately transferred to a vacuum dryer and dried at room temperature and below 10 kPa for 2-6 hours (e.g., 2 hours, 3 hours, 4 hours, 5 hours or 6 hours).
[0023] Preferably, the polyisocyanate includes any one or a combination of at least two of aliphatic polyisocyanates, alicyclic polyisocyanates, aryliphatic polyisocyanates, or aromatic polyisocyanates.
[0024] Preferably, the polyisocyanate contains any one or a combination of at least two of the following structures: diketone, isocyanurate, urethane, urethane, biuret, iminooxadiazine diketone, or oxadiazine triketone.
[0025] Preferably, the isocyanate used to prepare the polyisocyanate is selected from diisocyanates, wherein the diisocyanate is selected from one or a combination of at least two of the following: tetramethylene-1,4-diisocyanate, pentamethylene-1,5-diisocyanate, hexamethylene-1,6-diisocyanate, dodecamethylene-1,12-diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 4,4'-dicyclohexylpropane diisocyanate, 1,4-phenylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, tetramethylisophthalimethylene diisocyanate, or terephthalic diisocyanate.
[0026] Preferably, the tertiary amine is selected from any one or a combination of at least two of N,N-dimethylbutylamine, N,N-dimethyl-2-ethylhexylamine, N,N-diethylmethylamine, N,N-diisopropylethylamine, N,N-diisopropyl-2-ethylhexylamine, N,N-dimethylcyclohexylamine, N,N-dicyclohexylmethylamine, N-methylpyrrolidine, N-methylpiperidine, N-ethylpiperidine, N-methylmorpholine, N-ethylmorpholine, and N-isobutylmorpholine. The tertiary amine can be used to neutralize the sulfonic acid group in aminosulfonic acid to form a sulfonate, and simultaneously act as a phase transfer catalyst to catalyze the reaction between polyisocyanates and aminosulfonic acids.
[0027] Preferably, the amount of α-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid is 0.3-25% based on the total mass of polyisocyanate and α-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid as 100%, for example, 0.3%, 3%, 6%, 9%, 12%, 15%, 18% or 25%.
[0028] Preferably, the molar ratio of the tertiary amine to α-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid is 0.8-1.5:1, for example, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1 or 1.5:1, etc.
[0029] Preferably, the weight ratio of iminooxadiazine dione structure to isocyanurate structure in the hydrophilic modified polyisocyanate is ≥1 / 300, for example, it can be 1 / 280, 1 / 250, 1 / 230, 1 / 200, 1 / 180, 1 / 150, 1 / 130, 1 / 100, 1 / 80, 1 / 50, 1 / 30, 1 / 20, 1 / 10, 1 / 8, 1 / 5, 1 / 3, 1 / 2 or 1 / 1, etc.
[0030] Preferably, the amount of sulfonate in the hydrophilic modified polyisocyanate is 0.1-7.7 wt%, for example, 0.1 wt%, 0.5 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, 5 wt%, 5.5 wt%, 6 wt%, 6.5 wt%, 7 wt%, 7.5 wt%, or 7.7 wt%.
[0031] Preferably, the raw materials for preparing the hydrophilic modified polyisocyanate further include optional component D catalyst.
[0032] Preferably, the catalyst is selected from one or a combination of at least two of tertiary amine catalysts and organometallic catalysts that are different from component C; preferably, the tertiary amine catalyst may be selected, for example, but not limited to, one or a combination of at least two of pyridine, methylpyridine, benzyldimethylamine, and N,N-dimethylpiperazine. Preferably, the organometallic catalyst may be selected, for example, but not limited to, one or a combination of at least two of tri(ethyl-acetoacetic acid)aluminum, tin n-octanoate, zinc n-octanoate, tin(II) 2-ethyl-1-hexanoate, dibutyltin(IV) dichloride, dibutyltin(IV) diacetate, dibutyltin(IV) dilaurate, dioctyltin(IV) diacetate, or molybdenum glycolate. The amount of these conventional catalysts used can be easily determined by those skilled in the art based on the needs of the reaction, for example, 10-2000 ppm of the total weight of the reactants (e.g., 10 ppm, 80 ppm, 100 ppm, 200 ppm, 300 ppm, 400 ppm, 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm, 1000 ppm, 1110 ppm, 1210 ppm, 1310 ppm, 1410 ppm, 1510 ppm, 1610 ppm, 1710 ppm, 1810 ppm or 2000 ppm, etc.), preferably 100-500 ppm.
[0033] Preferably, the raw materials for preparing the hydrophilic modified polyisocyanate further include the optionally added component E solvent.
[0034] Preferably, the solvent may be selected from one or a combination of at least two of the following solvents: acetone, butanone, cyclopentanone, cyclohexanone, ethyl acetate, butyl acetate, tetrahydrofuran, N-methylpyrrolidone, N-ethylpyrrolidone, toluene, xylene, chlorobenzene, propylene glycol methyl ether acetate, 1-methoxy-2-propyl acetate, 3-methoxy-n-butyl acetate, aromatic compounds, dimethyl carbonate, diethyl carbonate, butyrolactone, caprolactone, or methylcaprolactone.
[0035] Preferably, the raw materials for preparing the hydrophilic modified polyisocyanate further include optional component F, an antioxidant.
[0036] Preferably, the antioxidant is selected from one or a combination of at least two of 2,6-di-tert-butyl-4-methylphenol, triisodecyl phosphite, phenyl diisodecyl phosphite, and diphenyl isodecyl phosphite. Those skilled in the art can readily determine the amount of antioxidant added according to actual needs; for example, the amount of antioxidant added may be 0%-1.5% of the total mass of polyisocyanate (a) and α-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid, such as 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.2%, or 1.5%.
[0037] On the other hand, the present invention provides a method for preparing the hydrophilic modified polyisocyanate as described above, the method comprising the following steps: Components A, B, C, and optional components D, E, and F are reacted to obtain the hydrophilic modified polyisocyanate.
[0038] Preferably, the reaction temperature is 70-130℃ (e.g., 70℃, 75℃, 80℃, 85℃, 90℃, 95℃, 100℃, 105℃, 110℃ or 130℃, etc.), and the reaction time is 3-12 hours (e.g., 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours or 12 hours, etc.).
[0039] On the other hand, the present invention provides the application of the hydrophilic modified polyisocyanate as described above in the preparation of waterborne polyurethane materials or blocked polyisocyanates.
[0040] On the other hand, the present invention provides the application of the hydrophilic modified polyisocyanate as described above in the preparation of waterborne two-component coatings or waterborne adhesives.
[0041] Compared with the prior art, the present invention has the following beneficial effects: This invention eliminates the need for additional hydroxycarboxylic acids. By using aminosulfonic acid with a specific crystal form to prepare water-dispersible polyisocyanates, it can significantly extend the pot life, improve the stain resistance of the coating film, shorten the reaction time, and reduce the turbidity and color of the product.
[0042] The hydrophilic modified polyisocyanate of this invention has a color number of 2-3 Hazen, a turbidity of 0.1-0.2 NTU, a pot life of 12-15 hours, and good stain resistance of the coating film. Compared with other crystal forms of 3-(cyclohexylamine)-1-propanesulfonic acid, under the same reaction temperature, the reaction time can be shortened by 4 times, the color number reduced by 43 times, the turbidity reduced by 150 times, the pot life extended by 4.8 times, and the stain resistance of the coating film is improved. Attached Figure Description
[0043] Figure 1 The X-ray diffraction pattern of β-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid is shown.
[0044] Figure 2 The X-ray diffraction pattern of γ-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid is shown.
[0045] Figure 3 The image shows the X-ray diffraction pattern of α-(cyclohexylamine)-1-propanesulfonic acid (i.e., self-made α-(cyclohexylamine)-1-propanesulfonic acid) prepared from β-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid in this invention.
[0046] Figure 4 Synchronous thermal analysis chromatogram of self-made α-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid.
[0047] Figure 5 This is a simultaneous thermal analysis chromatogram of β-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid.
[0048] Figure 6 The image shows the simultaneous thermal analysis of γ-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid.
[0049] Figure 7 Differential scanning calorimetry for self-made α-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid.
[0050] Figure 8 Differential scanning calorimetry for β-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid.
[0051] Figure 9 Differential scanning calorimetry (DSC) for γ-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid.
[0052] Figure 10 X-ray diffraction comparison images of self-made α-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid before and after baking at 130℃ for 12 hours. Detailed Implementation
[0053] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.
[0054] In this invention, the 3-(cyclohexylamine)-1-propanesulfonic acid used includes the following: β-Crystal form 3-(cyclohexylamine)-1-propanesulfonic acid: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., analytical grade, purity ≥98%; γ-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid: purchased from Shanghai Maclean Biochemical Technology Co., Ltd., analytical grade, purity ≥99%; Characterization of commercially available 3-(cyclohexylamine)-1-propanesulfonic acid (CAPS) using X-ray diffraction (XRD), simultaneous thermal analysis (TG-DSC), and differential scanning calorimetry (DSC) revealed that the 3-(cyclohexylamine)-1-propanesulfonic acid purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. is in the β-crystal form (X-ray diffraction pattern shown in Figure 1). Figure 1 As shown in the image, 3-(cyclohexylamine)-1-propanesulfonic acid, purchased from Shanghai Maclean Biochemical Technology Co., Ltd., is in the γ-crystalline form (X-ray diffraction pattern shown in the image). Figure 2 (As shown).
[0055] The present invention also recrystallizes β-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid (CAPS) purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. to prepare α-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid (CAPS).
[0056] Homemade α-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid (α-crystalline purity ≥90wt%): Under magnetic stirring at 1000 rpm, 20 g of 3-(cyclohexylamine)-1-propanesulfonic acid (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., purity ≥98%) was added to 80 mL of water. The mixture was then stirred at 50 °C for 30 min to completely dissolve the 3-(cyclohexylamine)-1-propanesulfonic acid in the water. The solution was then rapidly filtered. The filtrate was quickly poured into a container pre-cooled to 0 °C. Under magnetic stirring at 1000 rpm, 300 mL of acetone pre-cooled to 0 °C was added to the filtrate in one go within 30 seconds. A large amount of white precipitate was immediately observed to form. After stirring for another 10 min, the mixture was immediately vacuum filtered. The filter cake was then quickly washed with 60 mL of acetone at 0 °C. The filter cake was then quickly transferred to a vacuum desiccator and dried at room temperature and below 10 kPa for 2 hours to obtain α-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid.
[0057] The XRD pattern of α-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid is shown below. Figure 3 As shown.
[0058] The α-form of 3-(cyclohexylamine)-1-propanesulfonic acid has 2θ values of 5.473±0.2°, 5.936±0.2°, 9.139±0.2°, 10.574±0.2°, 10.970±0.2°, 11.221±0.2°, 11.903±0.2°, 14.518±0.2°, 14.866±0.2°, 15.994±0.2°, 16.494±0.2°, 17.585±0.2°, 17.890±0.2°, 18.754±0.2°, 19.011±0.2°, 21.296±0.2°, and 22.035±0.2°. Characteristic peaks are observed at 22.763±0.2°, 24.967±0.2°, 26.157±0.2°, 26.660±0.2°, 28.054±0.2°, 28.787±0.2°, 29.797±0.2°, 30.992±0.2°, 31.408±0.2°, 31.965±0.2°, 34.159±0.2°, 35.004±0.2°, and 36.530±0.2°, with the strongest diffraction peaks at 2θ values of 5.473±0.2° and / or 5.936±0.2°.
[0059] In addition, the self-made 3-(cyclohexylamine)-1-propanesulfonic acid was characterized by simultaneous thermal analysis (TG-DSC) and differential scanning calorimetry (DSC).
[0060] TG-DSC ( Figure 4 The test results showed that the self-made CAPS exhibited a 3.6% weight loss at approximately 75.6℃ (peak I) accompanied by an endothermic peak, indicating desorption of residual water or solvent; an endothermic peak was observed at approximately 222.9℃ (peak II) without any mass change, corresponding to the melting process of the α-crystal form; significant weight loss (93.38%) occurred at approximately 362.3℃ (peak III) and 369.4℃ (peak IV), accompanied by endothermic peaks, indicating that the compound underwent decomposition. (DSC curve) Figure 7 Further analysis showed that the α-crystal melting peak of the self-made CAPS was located at 224.7℃ (peak II), and the heat absorbed during the melting process was 35.29 J / g.
[0061] XRD patterns showed that 3-(cyclohexylamine)-1-propanesulfonic acid, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., exhibited a stronger diffraction peak at 2θ of 8.590±0.2°, distinct from the α-crystalline form, indicating a lower intensity of the α-crystalline form's related diffraction peak. This suggests that the sample primarily contains the β-crystalline form. The X-ray powder diffraction patterns of the β-crystalline form of 3-(cyclohexylamine)-1-propanesulfonic acid, measured using CuKa radiation, were observed at 2θ values of 8.590±0.2°, 13.401±0.2°, 13.812±0.2°, 15.319±0.2°, 17.218±0.2°, 18.476±0.2°, and 20.09°. Characteristic peaks are observed at 9±0.2°, 20.623±0.2°, 23.170±0.2°, 25.744±0.2°, 26.993±0.2°, 27.848±0.2°, 29.401±0.2°, 32.825±0.2°, 33.408±0.2°, 35.821±0.2°, and 37.436±0.2°. The DSC curve ( Figure 8 The data shows that Aladdin CAPS exhibits an endothermic characteristic peak at approximately 70.9℃ (peak I), which, combined with TG-DSC (…), indicates… Figure 5 The test results showed that the sample simultaneously experienced a 2.94% mass loss at this temperature, indicating that the thermogravimetric endothermic process was attributed to the desorption of adsorbed water or residual solvent. TG-DSC ( Figure 5 The results showed that Aladdin CAPS exhibited two endothermic peaks with no mass change at approximately 206.5℃ (peak II) and 222.8℃ (peak III). Since peak III occurred at the same temperature as the α-crystal melting peak of the self-made CAPS, it is presumed that peak III is the α-crystal melting peak. (DSC curve) Figure 8 Further measurements showed that peak II absorbed 35.23 J / g of heat, while the α-crystal form absorbed 31.4 J / g of heat upon melting (peak III). Since the α-crystal form of Aladdin CAPS and the self-made CAPS absorbed essentially the same amount of heat, it is speculated that peak II of Aladdin CAPS corresponds to the solid-solid phase transition from β-crystal to α-crystal. According to the Burger-Ramberger rule, the phase transition temperature of the β-crystal form is lower than the melting point of the α-crystal form, indicating that α and β-crystal forms are interconvertible. When the temperature is above the phase transition temperature of 206.5℃, the α-crystal form is more stable than the β-crystal form; when the temperature is below the phase transition temperature of 206.5℃, the β-crystal form is more stable than the α-crystal form. After baking the self-made CAPS at 130℃ for 12 hours, X-ray diffraction (XRD) tests were performed, and the results showed… Figure 10 The XRD patterns of the self-made CAPS before and after baking were basically the same, indicating that although the α-crystal form is relatively unstable in the 70-130℃ range, it still exists in the α-crystal form without undergoing a crystal transformation. TG-DSC ( Figure 5The results showed that Aladdin CAPS experienced significant weight loss (96.91%) at approximately 362.8℃ (peak IV) and 369.3℃ (peak V), accompanied by endothermic peaks, indicating that the compound decomposed.
[0062] The XRD pattern shows that Maclean CAPS exhibits a strong diffraction peak at 2θ of 7.848±0.2°, distinct from the α and β crystal forms, and the related diffraction peaks of the α and β crystal forms are relatively weak. This indicates that the sample mainly contains the γ crystal form. The X-ray powder diffraction pattern of the γ crystal form of 3-(cyclohexylamine)-1-propanesulfonic acid, measured using CuKa radiation, shows characteristic peaks at 2θ values of 7.848±0.2°, 15.542±0.2°, 15.766±0.2°, 16.842±0.2°, 19.787±0.2°, 21.707±0.2°, 22.303±0.2°, 23.917±0.2°, 24.354±0.2°, 24.587±0.2°, and 27.325±0.2°. The DSC curve (…) Figure 9 The results showed that the McLean Aladdin CAPS exhibited an endothermic characteristic peak at approximately 91.6 (peak I), which, combined with TG-DSC (…), indicated that… Figure 6 The test results showed that the sample simultaneously experienced a 3.57% mass loss at this temperature, indicating that the thermogravimetric endothermic process was attributed to the desorption of adsorbed water or residual solvent. Subsequent TG-DSC (...) Figure 6 Two endothermic peaks (peak II and peak III) without mass change were observed in the sample. Combined with DSC analysis (…), Figure 9 The two peaks, 207.7℃ (peak II) and 224.5℃ (peak III), correspond to the solid-solid phase transition from β to α crystal form and the melting process of α crystal form, respectively. The heat absorbed during the transition from β to α crystal form is 6.47 J / g, and the heat absorbed during the melting of α crystal form is 11.3 J / g. (DSC curve) Figure 9 The results showed that the McLean CAPS exhibited endothermic peaks at approximately 259.0℃ (peak IV) and 266.4℃ (peak V), which, combined with TG-DSC analysis ( Figure 6 At this temperature, the sample experienced an 18.86% mass loss, indicating that the process was attributed to the melting of the γ-form and the initial decomposition of the compound. Since the melting point of the γ-form (259.0℃) is higher than that of the α-form (224.5℃), the γ-form is more stable than the α-form. TG-DSC ( Figure 6 Further analysis showed that a 73.67% mass loss occurred at approximately 346.9℃ (peak VI) accompanied by an endothermic peak, indicating that the compound continued to decompose.
[0063] The particle size distribution of α-(cyclohexylamine)-1-propanesulfonic acid in α-, β-, and γ-forms was measured using a laser particle size analyzer. The results are shown in Tables 1 and 2 below.
[0064] Table 1 Table 2 Other components used in the embodiments are as follows: Component A1: NT3300, an HDI-based polyisocyanate with NCO content of 21.7-22.2 wt%, purchased from Shandong Xinhe Chengjing Chemical Technology Co., Ltd. Component A2: N3600, an HDI-based polyisocyanate with NCO content of 22.5-23.5 wt%, purchased from Covestro; Component A3: N3900, an HDI-based polyisocyanate with NCO content of 23.0-24.0 wt%, purchased from Covestro.
[0065] Component C: N,N-dimethylcyclohexylamine, purchased from Shanghai Maclean Biochemical Technology Co., Ltd., with a purity ≥98%.
[0066] The testing methods and standards used in the embodiments of this invention are as follows: 1. NCO content testing standard: GB / T 12009.4-2016.
[0067] 2. Viscosity test standard: GB / T 21059-2007. The test shall be conducted using a rotational rheometer.
[0068] 3. Color number testing standard: GB / T 1722-1992. Measurements were taken using an EC2000-Pt-Co colorimeter with a Hazen scale.
[0069] 4. Turbidity test standard: GB5749-2022. Measured using a HACH 2100Q Portable Turbidimeter, unit: NTU.
[0070] 5. Pot life test method: Mix 18g of water-dispersible polyisocyanate, 60g of Bayhydrol® XP2470, 10g of deionized water, 0.16g of AMP 95, 0.33g of TEGO® Dispers 750 W, and 0.41g of TEGO® Foamex 810 until homogeneous to obtain the water-based coating. Then, let the coating stand at room temperature. The time it takes for the coating viscosity to double its initial viscosity is defined as the pot life of the coating. (Bayhydrol® XP2470: A polyacrylic acid dispersion containing hydroxyl functional groups, purchased from Covestro. AMP 95: Also known as 2-amino-2-methyl-1-propanol, an amine neutralizer, purchased from Dow Chemical. TEGO® Dispers 750 W: A weakly anionic polymer wetting and dispersing agent for high-performance aqueous formulations, purchased from Evonik. TEGO® Foamex 810: A highly efficient defoamer concentrate based on polyether siloxane technology, purchased from Evonik.)
[0071] 6. Stain Resistance Test Method: GB / T 4893.1-2005. The water-based coating used in the pot life test is sprayed onto light-colored white beech wood with a film thickness of 50 micrometers. After application, it is allowed to dry at room temperature for 30 minutes, then placed in a 60℃ oven for 2 hours. It is then placed at 25℃ and 50% relative humidity for one week before testing the stain resistance of the coating. Stain resistance test procedure: The test solution is vinegar / green tea. Five layers of filter paper are placed between the coated wood panels. The filter paper is kept moist during the test. After 24 hours, the filter paper is removed. If no blistering, cracking, or peeling is observed after 2 hours, it is rated as "no abnormalities," indicating good stain resistance of the coating.
[0072] 7. XRD testing standard: General Chapter 0451, Part IV, Chinese Pharmacopoeia 2020 Edition. Powder X-ray diffraction instrument used: Bruker D8 Advance.
[0073] 8. DSC testing standard: General Chapter IV of the 2020 edition of the Chinese Pharmacopoeia, 0661 Thermal Analysis Method. Differential scanning calorimeter was used, instrument model NETZSCH DSC 204F1.
[0074] 9. Simultaneous Thermal Analysis (TG-DSC) Test Standard: General Chapter IV, 2020 Edition of the Chinese Pharmacopoeia, 0661 Thermal Analysis Method. A simultaneous thermal analyzer, model NETZSCH STA 449F3, was used.
[0075] 10. LPSA testing standard: Chinese Pharmacopoeia 2020 Edition, Part IV, General Chapter, 0982, Particle Size and Particle Size Distribution Determination, Method III (Light Scattering Method). A laser particle size analyzer, model Microtrac SYNC, was used.
[0076] 11. The weight ratio of the iminooxadiazine dione structure to the isocyanurate structure in the polyisocyanate was determined by 13CNMR. The testing instrument was a Bruker Avance Ⅲ HD 400M. The weight ratio of the iminooxadiazine dione structure to the isocyanurate structure = 1:(integrated area@148.9ppm) / (integrated area@148.3ppm + integrated area@144.9ppm + integrated area@135.5ppm). In the reaction for preparing modified polyisocyanate from polyisocyanate of the present invention, the weight ratio of the iminooxadiazine dione structure to the isocyanurate structure in the modified polyisocyanate is the same as the weight ratio of the iminooxadiazine dione structure to the isocyanurate structure in the polyisocyanate.
[0077] 12. Sulfonate content in the product (expressed as SO₂) 3- Calculation (molecular weight = 80), obtained through theoretical calculation: Sulfonate content = molar amount of aminosulfonic acid × 80 / product mass × 100%.
[0078] Example 1 Preparation method of aminosulfonic acid modified polyisocyanate: 400g of component A1 (NT3300), 13.4g of α-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid and 7.70g of component C (N,N-dimethylcyclohexylamine) were reacted at 90°C for 3 hours, the reaction was stopped, the mixture was filtered under reduced pressure using a 350-mesh filter, and then cooled to room temperature to obtain aminosulfonic acid modified polyisocyanate.
[0079] NCO content: 20.04 wt%; Viscosity (23℃): 6517 mPa·s; Color number: 2; Turbidity: 0.1; Sulfonate content: 1.15 wt% The weight ratio of the iminooxadiazine dione structure to the isocyanurate structure is 1:22.12.
[0080] Examples 1-6: Except for the type and amount of component A, the amount of α-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid, and the amount of component C, all other conditions were the same as in Example 1.
[0081] Table 3 The product performance test results of the aminosulfonic acid modified polyisocyanate prepared in the examples are shown in Table 4.
[0082] Table 4 As can be seen from Examples 1-6, using α-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid to prepare polyisocyanates of different systems, the hydrophilic modified polyisocyanates obtained by reacting at 90°C for 3 hours have a color number of 2-3 Hazen, a turbidity of 0.1-0.2 NTU, a pot life of 12-15 hours, and good stain resistance of the coating film.
[0083] Comparative Examples 1-2: Except for the different crystal forms of 3-(cyclohexylamine)-1-propanesulfonic acid, all other conditions were the same as in Example 1.
[0084] Table 5 The product performance test results of the aminosulfonic acid modified polyisocyanate prepared in the comparative example are shown in Table 6.
[0085] Table 6 As shown in Comparative Examples 1-2, when polyisocyanates are prepared using β- and γ-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid at 90°C for 12 hours, the resulting product has a color number of 130-135 Hazen, a turbidity of 30-40 NTU, a pot life of 2-2.5 hours, and poor stain resistance. However, when polyisocyanates are prepared using α-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid at the same reaction temperature, the reaction time is shortened by 4 times, the color number is reduced by 43 times, the turbidity is reduced by 150 times, the pot life is extended by 4.8 times, and the stain resistance of the coating is improved.
[0086] Furthermore, in terms of particle size distribution, 90% of the particles in α-, β-, and γ-form 3-(cyclohexylamine)-1-propanesulfonic acid have a particle size ≤100 μm. Therefore, when the particle size distribution of 3-(cyclohexylamine)-1-propanesulfonic acid is similar, by controlling the crystal form of 3-(cyclohexylamine)-1-propanesulfonic acid in the reaction system to be α-form, hydrophilic modified polyisocyanates with smaller color numbers, lower turbidity, longer pot life, and better stain resistance can be obtained with a relatively shorter reaction time. This indicates that, compared to the particle size of aminosulfonic acid, its crystal form has a more critical impact on the reaction rate, product turbidity, color, pot life, and stain resistance of the hydrophilic modified polyisocyanate system.
[0087] In summary, 3-(cyclohexylamine)-1-propanesulfonic acid exists in multiple crystal forms. During the preparation of sulfonate-modified polyisocyanates (reaction temperature 70-130℃), the γ-crystalline form of 3-(cyclohexylamine)-1-propanesulfonic acid is more stable than the α-crystalline form, and the β-crystalline form is more stable than the α-crystalline form. Because the less stable crystal forms dissolve faster, have higher solubility, and react more completely during the reaction, they can achieve uniform dispersion and grafting of the hydrophilic agent. Therefore, using the α-crystalline form of 3-(cyclohexylamine)-1-propanesulfonic acid (self-made sample) can yield a clear, transparent, and uniformly modified hydrophilic product. This modified product has a uniform distribution of free NCO groups and exhibits a moderate reaction rate when crosslinking with hydroxyl resins, significantly extending its pot life. Meanwhile, the cured coating exhibits high cross-linking density and a continuous, dense structure, effectively preventing contaminant penetration and thus enhancing its stain resistance. In contrast, β- and γ-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid is stable, but its slow dissolution rate, low solubility, incomplete reaction, and uneven distribution within the system during the reaction easily lead to residues. This results in a cloudy appearance and uneven distribution of NCO groups in the hydrophilic modified product. Regions with locally enriched NCO groups in the hydrophilic modified product react too quickly and prematurely with the hydroxyl resin, causing a rapid increase in system viscosity and shortening the pot life. Conversely, sparsely distributed NCO groups result in insufficient cross-linking, causing defects and pores on the coating surface. Stains easily penetrate and are difficult to remove, significantly reducing the coating's stain resistance.
[0088] The applicant declares that this invention illustrates the hydrophilic modified polyisocyanate, its preparation method, and its application through the above embodiments. However, this invention is not limited to the above embodiments, meaning that this invention does not necessarily rely on the above embodiments for implementation. Those skilled in the art should understand that any improvements to this invention, equivalent substitutions of the raw materials used, additions of auxiliary components, and selection of specific methods all fall within the protection and disclosure scope of this invention.
Claims
1. A hydrophilic modified polyisocyanate, characterized in that, The hydrophilic modified polyisocyanate is prepared by reacting raw materials comprising the following components; Component A: polyisocyanate, component B: α-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid, and component C: tertiary amine.
2. The hydrophilic modified polyisocyanate according to claim 1, characterized in that, The X-ray powder diffraction pattern of the α-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid, measured using CuKa rays, showed 2θ values of 5.473±0.2°, 5.936±0.2°, 9.139±0.2°, 10.574±0.2°, 10.970±0.2°, 11.221±0.2°, 11.903±0.2°, 14.518±0.2°, 14.866±0.2°, 15.994±0.2°, 16.494±0.2°, 17.585±0.2°, 17.890±0.2°, 18.754±0.2°, and 19.011±0.2°. Characteristic peaks are observed at 21.296±0.2°, 22.035±0.2°, 22.763±0.2°, 24.967±0.2°, 26.157±0.2°, 26.660±0.2°, 28.054±0.2°, 28.787±0.2°, 29.797±0.2°, 30.992±0.2°, 31.408±0.2°, 31.965±0.2°, 34.159±0.2°, 35.004±0.2°, and 36.530±0.2°. Preferably, the X-ray powder diffraction pattern of the α-crystal form of 3-(cyclohexylamine)-1-propanesulfonic acid, measured using CuKa rays, has the strongest diffraction peak at 2θ values of 5.473±0.2° and / or 5.936±0.2°.
3. The hydrophilic modified polyisocyanate according to claim 1 or 2, characterized in that, In the particle size distribution of the α-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid, the content of particles with a diameter ≤16μm accounts for ≥25%.
4. The hydrophilic modified polyisocyanate according to any one of claims 1-3, characterized in that, The polyisocyanate includes any one or a combination of at least two of aliphatic polyisocyanates, alicyclic polyisocyanates, aryliphatic polyisocyanates, or aromatic polyisocyanates. Preferably, the polyisocyanate contains any one or a combination of at least two of the following structures: urea diketone, isocyanurate, urethane, urethane, biuret, iminooxadiazine diketone, or oxadiazine triketone. Preferably, the isocyanate used to prepare the polyisocyanate is selected from diisocyanates, wherein the diisocyanate is selected from one or a combination of at least two of the following: tetramethylene-1,4-diisocyanate, pentamethylene-1,5-diisocyanate, hexamethylene-1,6-diisocyanate, dodecamethylene-1,12-diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 4,4'-dicyclohexylpropane diisocyanate, 1,4-phenylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, tetramethylisophthalimethylene diisocyanate, or terephthalic diisocyanate. Preferably, the tertiary amine is selected from any one or a combination of at least two of N,N-dimethylbutylamine, N,N-dimethyl-2-ethylhexylamine, N,N-diethylmethylamine, N,N-diisopropylethylamine, N,N-diisopropyl-2-ethylhexylamine, N,N-dimethylcyclohexylamine, N,N-dicyclohexylmethylamine, N-methylpyrrolidine, N-methylpiperidine, N-ethylpiperidine, N-methylmorpholine, N-ethylmorpholine, and N-isobutylmorpholine.
5. The hydrophilic modified polyisocyanate according to any one of claims 1-4, characterized in that, Based on the total mass of polyisocyanate and α-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid as 100%, the amount of α-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid is 0.3-25%; Preferably, the molar ratio of the tertiary amine to α-crystalline 3-(cyclohexylamine)-1-propanesulfonic acid is 0.8-1.5:1; Preferably, the weight ratio of iminooxadiazine dione structure to isocyanurate structure in the hydrophilic modified polyisocyanate is ≥1 / 300; Preferably, the amount of sulfonate in the hydrophilic modified polyisocyanate is 0.1-7.7 wt%.
6. The hydrophilic modified polyisocyanate according to any one of claims 1-5, characterized in that, The raw materials for preparing the hydrophilic modified polyisocyanate also include component D catalyst; Preferably, the catalyst is selected from one or a combination of at least two of tertiary amine catalysts and organometallic catalysts that are different from the component C; Preferably, the tertiary amine catalyst comprises one or a combination of at least two of pyridine, methylpyridine, benzyl dimethylamine, and N,N-dimethylpiperazine; Preferably, the organometallic catalyst is selected from one or a combination of at least two of the following: aluminum tri(ethyl-acetoacetate), tin n-octanoate, zinc n-octanoate, tin (II) 2-ethyl-1-hexanoate, dibutyltin dichloride (IV), dibutyltin diacetate (IV), dibutyltin dilaurate (IV), dioctyltin diacetate (IV), or molybdenum glycolate; Preferably, the raw materials for preparing the hydrophilic modified polyisocyanate further include component E solvent; Preferably, the solvent may be selected from one or a combination of at least two of the following solvents: acetone, butanone, cyclopentanone, cyclohexanone, ethyl acetate, butyl acetate, tetrahydrofuran, N-methylpyrrolidone, N-ethylpyrrolidone, toluene, xylene, chlorobenzene, propylene glycol methyl ether acetate, 1-methoxy-2-propyl acetate, 3-methoxy-n-butyl acetate, aromatic compounds, dimethyl carbonate, diethyl carbonate, butyrolactone, caprolactone, or methylcaprolactone. Preferably, the raw materials for preparing the hydrophilic modified polyisocyanate further include component F, antioxidant; Preferably, the antioxidant is selected from one or a combination of at least two of 2,6-di-tert-butyl-4-methylphenol, triisodecyl phosphite, phenyl diisodecyl phosphite, and diphenyl isodecyl phosphite.
7. A method for preparing the hydrophilic modified polyisocyanate according to any one of claims 1-6, characterized in that, The preparation method includes the following steps: Components A, B, C, and optional components D, E, and F are reacted to obtain the hydrophilic modified polyisocyanate.
8. The preparation method according to claim 7, characterized in that, The reaction temperature is 70-130℃, and the reaction time is 3-12 hours.
9. The use of the hydrophilic modified polyisocyanate according to any one of claims 1-6 in the preparation of waterborne polyurethane materials or blocked polyisocyanates.
10. The use of the hydrophilic modified polyisocyanate according to any one of claims 1-6 in the preparation of waterborne two-component coatings or waterborne adhesives.
Citation Information
Patent Citations
A kind of aminosulfonic acid modified polyisocyanate and its preparation method and application
CN116178672B
Modified polysocyanates
CN1190450C